The influence of socioeconomic deprivation on early outcomes in vascular access surgery. Issue 6 (November 2015) - Khalid, Usman; Powell-Chandler, Anna; Sabah, Tarique; Horvath, Szabolcs; Morris, Rhys; Ilham, Mohamed A.; Stephens, Michael R.
Introduction: Socioeconomic deprivation is an important factor in determining poor health and is associated with a higher prevalence of many chronic diseases including diabetes and renal failure, and often poorer outcomes for patients with such conditions. The influence of deprivation on outcomes following vascular access surgery has not previously been reported. Methods: The Welsh Index of Multiple Deprivation was used to assess the influence of socioeconomic deprivation on outcomes following 507 consecutive first upper limb arteriovenous (AV) fistulas from a single institution in the United Kingdom, performed between 2011 and 2014. The primary outcome measures were early failure and maturation into a working fistula. Results: Four hundred and five (80%) patients had a patent AV fistula at the 2-week follow-up clinic. Three hundred and fifty-nine (71%) patients developed a functionally mature AV fistula as determined by clinical assessment and a Doppler scan. There were no differences in either early failure rates ( p = 0.95) or maturation rates ( p = 0.77) between the least and most deprived groups of patients. Conclusions: In conclusion, this study has shown that socioeconomic deprivation does not influence outcomes following vascular access surgery.